State of knowledge and future research needs on microplastics in groundwater - Amélie Hoarau Belkhiri; Florence Carre; Fabrice Quiot (Journal of Water and Health, 2022)
Microplastics (MPs) are widespread in aquatic and soil environments. This study targets the issue of MPs’ transfer from soil to groundwater. Scientific papers were collected and analyzed using a text-mining approach that classifies text segments. This allowed the identification of four research topics and the organization of the results into a summarizing table. Those four topics are sources of groundwater MPs, main types of MPs (physico-chemical properties, polymer units, shapes, and size), human exposure (mainly drinking water), and potential environmental and human effects. Compared to the research of MP on aquatic or soil compartments, scientific data on MP in groundwater are less substantial. Current results show a divergence due to differences in context (alluvial aquifer, fractured rock aquifer, karst aquifer, etc), collecting, sampling, and analytical methods. This divergence requires further research with standardized analytic protocols and reference materials. The associated research gaps were identified by using the same approach. The following five topics emerged: (1) the transfer of MPs from soil to underground, (2) the contribution of groundwater to drinking water microplastic pollution, (3) the interaction with other contaminants, (4) the human and environmental effects, and (5) the protective and remediation solutions. HIGHLIGHTS A text-mining tool was used to distinguish sources, types, exposure pathways, and effects of microplastics (MPs).; There is a lack of common criteria to compare the behavior of MP in groundwater and their potential environmental and health impacts.; There is a need for standardized sampling, extracting, and analytical methods on microplastics in groundwater and biological matrices.;